Subsoil nitrogen capture in mixed legume stands as assessed by deep nitrogen-15 placement - Gathumbi, Stanley M.; Cadisch, Georg; Buresh, Roland J.; Giller, Ken E. (Wiley, 2003)
The rotation of crops with planted N2–fixing legumes (improved fallows) is a promising agroforestry innovation for replenishing soil fertility in the tropics. We postulated that woody and herbaceous legumes with different rooting and growth patterns could be mixed in improved fallows to maximize utilization of belowground growth resources. We used a method of injecting a solution of 15N‐labeled (NH4)2SO4 into soil at 0.15‐ and 1.0‐m depths to measure soil mineral N acquisition by sesbania [Sesbania sesban (L) Merr], crotalaria [Crotalaria grahamiana Wight and Arn.], and the understory herbaceous legume siratro [Macroptilium atropurpureum (DC.) Urb.] grown in mixed stands on a Kandiudalfic Eutrudox soil in western Kenya. Crotalaria had the highest root length in the topsoil. Sesbania on the other hand had nearly half its total root length below 0.3 m at 0.3‐ to 1.5‐m depth; sesbania took up more added 15N than crotalaria and siratro from the 1.0‐m depth. Mixed sesbania and crotalaria stands, as compared with growing species in monocultures, increased root length at the 0.3‐ to 1.2‐m depth. Sesbania mixed with siratro was more effective than sesbania mixed with crotalaria in uptake of 15N at 1.0‐m depth but not at 0.15‐m depth. At 2 mo after injection, the 15N was concentrated immediately below the injection point with little lateral movement. This confirmed the utility of the methodology in determining temporal N uptake for species in mixed stands. Our results suggest that opportunities exist for enhanced subsoil N retrieval through the mixing of leguminous species, which can influence root distribution and increase rooting in the subsoil.